Feeling the Heat: Effects of Stress, Commitment, and Job Experience on Job Performance - Hunter, Larry W.; Thatcher, Sherry M. B. (Academy of Management Journal, 2007)
We examine the relationships between bank branch employees' felt job stress, organizational commitment, job experience, and performance. Our findings are consistent with the attention view of stress. Employees with higher levels of affective commitment and higher levels of job experience channeled felt stress more effectively into sales performance. Felt stress had neutral to negative effects on performance for employees with lower levels of commitment and job experience. Commitment, like stress, was more strongly related to performance when employees had more job experience. The results suggest that consideration of moderators of the stress-performance relationship is important both theoretically and practically.